Creative writing exercises for dummies : a Wiley brand - Hamand, Maggie, 1953- (For dummies. A Wiley brand, 2014)
Written by the founder of the Complete Creative Writing Course at London's Groucho Club, this activity-based guide walks you through the process of developing and writing in a wide range of genres including novels, short stories and creative nonfiction. The book includes writing prompts, exercises, mind maps, flow charts and diagrams designed to get your ideas flowing. You'll get expert guidance into character development, plot structure and prose, plus extensive insight into self-editing and polishing your work whether you're a new writer with a seed of an idea you would like to develop, or are looking to strengthen your creative writing skills.